A composite protective device and a preparation method and application thereof
Patent Information
- Application Number
- CN202510065658.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-01-16
AI Technical Summary
然而,传统UHPC在面对强冲击或高能侵彻时仍存在一定的局限性
1.本发明基于仿生结构提出了一种复合防护装置,借鉴自然界中龟壳等多边形单元的拼接结构,设计出模块化的六边形框架单元结构,将UHPC-CA材料分隔为多个独立单元,每个单元之间通过弹性材质外圈间隔。该设计能够有效限制径向裂缝的扩展,并通过邻接单元的相互约束,提升整体抗侵彻能力。密铺图形,特别是六边形单元间的紧密结合使得外力在多个方向上分散,从而阻止材料破坏的发生。密铺图形框架的弹性材质具有高弹性和吸能特性,显著减缓了冲击波的传播和裂纹的扩展。框架单元内部设有金属硬质骨架,公母槽结构增加了UHPC-CA单元与密铺图形框架之间的接触面积,提升了粘结强度,金属硬质骨架提升了整个结构的稳定性,金属硬质骨架与弹性材质形成软包硬的结构。从而通过多种材质与结构的合理布局与相互作用进一步提高防护性能。
Smart Images

Figure CN119803190B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of bulletproof technology, and in particular to a composite protective device, its preparation method, and its application. Background Technology
[0002] With the advancement of weaponry technology, the need for protection of buildings and facilities has become increasingly urgent. Faced with increasingly complex external threats, how to enhance the penetration resistance of building materials has become an important research direction in the field of protective engineering.
[0003] Ultra-high performance concrete (UHPC) has been widely used in protective engineering due to its superior mechanical properties, durability, crack resistance, and toughness. However, traditional UHPC still has certain limitations when facing strong impacts or high-energy penetration. Ultra-high performance concrete with coarse aggregate (UHPC-CA) has become an effective solution to improve penetration resistance. The introduction of coarse aggregate not only enhances the impact and penetration resistance of building materials through the strength and hardness of the aggregate itself, but also further improves energy absorption through the interfacial effect between the aggregate and the concrete matrix. Compared with UHPC without coarse aggregate, UHPC-CA exhibits more efficient impact resistance in impact failure modes.
[0004] Despite significant progress in improving penetration resistance, UHPC-CA remains a major technical challenge in the field of protective materials, particularly in optimizing its structural design to further enhance its performance. Improving the material structure and devices to more effectively absorb and disperse impact energy and limit the damage range in the face of more complex and higher-energy impacts, thereby enhancing overall protective performance, has become a research hotspot in this field. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide a composite protective device, its preparation method, and its application. By using a closely spaced splicing structure to divide UHPC-CA material into multiple independent units, with elastic materials separating the independent units, the advantages of UHPC-CA and elastic materials can be combined to further improve the device's anti-penetration performance.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solution: The first aspect of the present invention provides a composite protective device, comprising a tiled pattern frame and UHPC-CA units filled in the tiled pattern frame; the tiled pattern frame comprises an elastic material; the tiled pattern frame is laterally spliced with the UHPC-CA units; the elastic material is silicone rubber or nitrile rubber; The raw materials for preparing the UHPC-CA unit include 360-520 parts of cement, 36-52 parts of silica fume, 36-52 parts of fly ash, 800-1000 parts of fine aggregate, 800-1000 parts of coarse aggregate, 39-78 parts of steel fiber, 120-130 parts of water, and 5-10 parts of high-efficiency water-reducing agent.
[0007] A second aspect of the present invention provides a method for preparing the above-mentioned composite protective device, comprising the following steps: S1. Prepare UHPC-CA units of a predetermined shape; S2. Prepare a tiling pattern framework of a specified shape; S3. Assemble the UHPC-CA unit into the tiled pattern frame to obtain the composite protection device.
[0008] Thirdly, the present invention provides the application of the above-mentioned composite protective device in protective facilities.
[0009] The beneficial effects of this invention are as follows: 1. This invention proposes a composite protective device based on biomimetic structures. Drawing inspiration from the splicing structure of polygonal units such as tortoise shells in nature, a modular hexagonal frame unit structure is designed, dividing the UHPC-CA material into multiple independent units, each separated by an outer ring of elastic material. This design effectively limits the propagation of radial cracks and enhances overall penetration resistance through the mutual constraint of adjacent units. The tiling pattern, especially the tight bonding between the hexagonal units, disperses external forces in multiple directions, thus preventing material damage. The elastic material of the tiling pattern frame possesses high elasticity and energy absorption properties, significantly slowing the propagation of shock waves and crack expansion. An internal rigid metal skeleton is incorporated into the frame unit. The male-female groove structure increases the contact area between the UHPC-CA unit and the tiling pattern frame, improving bonding strength. The rigid metal skeleton enhances the stability of the entire structure, forming a soft-wrapped-hard structure with the elastic material. Thus, the rational layout and interaction of various materials and structures further improve protective performance.
[0010] 2. The structure provided by this invention adopts a modular design, which facilitates mass production and rapid on-site assembly. Each UHPC-CA unit is fixed to the others through an embedded structure of a closely spaced graphic frame, and a complete protective system is formed by the pouring and hardening of UHPC-CA grout. This prefabricated structure not only improves construction efficiency but also facilitates later inspection and maintenance, possessing excellent operability.
[0011] 3. The composite protective device provided by this invention can reduce the amount of UHPC-CA and lighten the overall structural weight while achieving the same penetration resistance. This lightweight design can reduce the building's self-weight and improve material utilization without affecting the protective performance, making it suitable for protective facilities with strict weight restrictions. Attached Figure Description
[0012] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0013] The diagram exaggerates the spacing or dimensions between parts to show their positions; the diagram is for illustrative purposes only.
[0014] Figure 1 This is a schematic diagram illustrating the design concept of the composite protection device in Example 1.
[0015] Figure 2 This is a schematic diagram of the connection structure of the molding die in Example 1.
[0016] Figure 3 This is a schematic diagram of the tiling graphic frame in Example 1.
[0017] Figure 4 This is a schematic diagram of the composite protection device in Example 1.
[0018] Figure 5 This is a cross-sectional structural diagram of the composite protective device in Example 4.
[0019] Figure 6 This is a cross-sectional structural diagram of the composite protective device in Example 5.
[0020] Among them, 1. Tiled graphic frame; 11. Groove; 12. Elastic material; 2. UHPC-CA unit; 3. Elastic body; 4. Metal rigid skeleton; 41. Hexagonal border. Detailed Implementation
[0021] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0022] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0023] The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0024] A composite protective device includes a tiled pattern frame and UHPC-CA units filled within the tiled pattern frame; the tiled pattern frame comprises an elastic material; the tiled pattern frame and the UHPC-CA units are laterally spliced; the elastic material is silicone rubber or nitrile rubber; the tiled pattern frame includes a rigid metal skeleton, and the rigid metal skeleton and the UHPC-CA units are separated by the elastic material; The raw materials for preparing the UHPC-CA unit include 360-520 parts of cement, 36-52 parts of silica fume, 36-52 parts of fly ash, 800-1000 parts of fine aggregate, 800-1000 parts of coarse aggregate, 39-78 parts of steel fiber, 120-130 parts of water, and 5-10 parts of high-efficiency water-reducing agent.
[0025] Through the above design, the geometric arrangement of the tiling pattern can effectively disperse external impact forces, and the mutual constraint between the tiling pattern frame and the UHPC-CA unit can delay structural failure. By utilizing the buffering effect of the elastic material and the high strength performance of UHPC-CA, stress dispersion and energy dissipation are achieved when the material is subjected to impact or penetration, effectively improving its overall penetration resistance. The UHPC-CA unit prepared from the above raw materials has high penetration resistance, and includes coarse aggregate and steel fiber, which can effectively reduce its shrinkage, so that the prepared UHPC-CA unit can conform to the spatial shape in the tiling pattern frame.
[0026] Optionally, the elastic material has an elastic modulus between 0.1 MPa and 10 MPa and a Shore hardness range of A30 to A80, giving it good energy absorption effect and good toughness. It can effectively absorb and disperse energy under impact, and its rigidity can firmly fix and support the UHPC-CA unit that is laterally spliced therein.
[0027] Optionally, the tiling pattern frame includes a rigid metal skeleton, which is separated from the UHPC-CA unit by an elastic material to ensure the stability of the entire structure under impact; the rigid metal skeleton is made of high-strength steel with a tensile strength of 600~1200MPa and a yield strength of 500~1000MPa.
[0028] Optionally, the outer perimeter of the rigid metal frame is covered with an elastic material, making the tiled graphic frame a soft-wrapped-hard structure to enhance the energy absorption and energy dispersion effect of the tiled graphic frame and limit the expansion of cracks; or, the rigid metal frame includes multiple interlocking polygonal frames, with elastic material spaced between the polygonal frames and the internal UHPC-CA units, so that the numerous polygonal frames can more flexibly form a protective device.
[0029] Optionally, the shape of the tiling pattern frame is one or more of triangles, quadrilaterals, and hexagons, which can be spliced into a plane by multiple shapes. The shape of the tiling pattern frame is composed of multiple straight line segments, so that the edges of the UHPC-CA unit are straight, making the overall structure design of the composite protective device convenient and easy to manufacture, and the proportion of elastic material in the composite protective device can be adjusted by adjusting the number of sides of the pattern.
[0030] Optionally, the tiling pattern frame and the UHPC-CA unit are spliced together by lateral male and female grooves. The male and female grooves include grooves and bosses. The height of the bosses is the same as the depth of the grooves. The lateral male and female groove structure can increase the contact area between the UHPC-CA unit and the tiling pattern frame. The snap-fit structure formed by the grooves and bosses improves the splicing strength to ensure the stability of the overall structure.
[0031] The side length of a UHPC-CA unit is 10 to 20 times the side-to-side spacing of adjacent UHPC-CA units. The side-to-side spacing is the wall thickness of the tiling pattern frame. Combined with the shape design of the tiling pattern, the proportion of elastic material and UHPC-CA material in the plane can be flexibly adjusted to meet different penetration resistance requirements.
[0032] Optionally, the composite protective device has a uniform thickness structure and can be installed as armor on the outer surface of a building.
[0033] Optionally, the height of the tiling pattern frame and the UHPC-CA unit is 30~100mm, that is, the overall thickness of the composite protective device is 30~100mm. Its planar dimensions can be increased by increasing the number of tiling patterns. When the tiling pattern is a regular hexagon, the side length of the UHPC-CA unit is 100~200mm, the distance between opposite sides of adjacent UHPC-CA units is 5~20mm, the depth of the groove in the male and female grooves is 3~5mm, and the height of the boss is the same as that of the groove, so that the two can be spliced together, thereby enabling the two to deform together, thus effectively utilizing the elasticity and energy absorption characteristics of the tiling pattern frame, significantly slowing down the propagation of shock waves and hindering the expansion of cracks in different UHPC-CA units.
[0034] Optionally, compared with the raw materials for preparing the UHPC-CA unit, the UHPC material does not contain coarse aggregate and steel fiber, and can fill the gap between the UHPC-CA unit and the tiled pattern frame to improve the lateral splicing strength; other raw materials are the same as those for preparing the UHPC-CA unit, which can improve the connection strength between the UHPC material as an adhesive and the UHPC-CA unit.
[0035] Optionally, the coarse aggregate is one or more of basalt, sintered bauxite, and corundum, which has high hardness to enhance the penetration resistance of the composite protective device.
[0036] The preparation method of the above-mentioned composite protective device includes the following steps: S1. Prepare UHPC-CA units of a predetermined shape; S2. Prepare a tiling pattern framework of a specified shape; S3. Assemble the UHPC-CA unit into the tiled pattern frame to obtain the composite protection device.
[0037] Optionally, in S1, UHPC-CA units are cast in a rigid mold, the inner cavity of which has the same shape as the inner cavity of the tiled pattern frame. After solidification and curing, the UHPC-CA units obtained have the same assembly space dimensions as the tiled pattern frame. The rigid mold is made of rigid plastic or metal, and its inner cavity dimensions are equal to the inner cavity shape dimensions of the tiled pattern frame. Since the shrinkage of UHPC-CA is relatively small due to the influence of coarse aggregate, the inner cavity shape dimensions do not need to take into account the shrinkage of UHPC-CA.
[0038] Optionally, the fabrication method of the UHPC-CA unit includes: S11. Mix cement, fly ash, silica fume, fine aggregate and coarse aggregate in a dry mix to obtain a dry mix material; S12. Add water and water-reducing agent to the dry mixture, stir initially, then add steel fibers and stir evenly. S13. Pour the UHPC-CA slurry into a rigid mold, remove air bubbles, and then cure it.
[0039] Optionally, the dry mixing time in S11 is 1-2 minutes and the mixing speed is 60 r / min; the initial mixing time in S12 is 2-4 minutes and the mixing speed is 120 r / min; after adding steel fibers, the mixing speed is 120 r / min and the mixing time is 2.5-4 minutes; and the mixing speed before pouring in S13 is 150 r / min and the mixing time is 2-3 minutes.
[0040] Optionally, in S13, a scraper and vibrator are used to remove air bubbles and improve density; the vibrator vibrates at a frequency of 30Hz for 3 minutes; the curing conditions are standard curing, with a temperature of 20±2℃ and humidity ≥95%; after demolding, a concrete grinder is used to polish the surface to eliminate imperfections and adjust the dimensions to prepare a dense UHPC-CA unit.
[0041] Optionally, in S2, a rigid metal skeleton is first prepared, and then a tiling pattern frame is prepared around the rigid metal skeleton by injection molding. This is a conventional forming method for wrapping a rigid skeleton with an elastic material.
[0042] Optionally, in S3, after the tiled pattern frame undergoes elastic deformation to expand the inner cavity size, it is assembled into the UHPC-CA unit one by one through the male and female slots, and then the tiled pattern frame is restored to its shape to complete the assembly of the two.
[0043] Optionally, in S3, UHPC slurry is filled into the gap between the UHPC-CA unit and the tiled pattern frame. After the slurry cures, the composite protective device is obtained. Then, the UHPC-CA unit and the tiled pattern frame become a tightly integrated whole, which can work together to resist impact and deformation.
[0044] Example 1 A composite protective device, with overall dimensions of approximately 800mm × 800mm × 50mm, such as... Figure 1 As shown, the tiling pattern frame includes 7 regular hexagonal cavities of the same size, each cavity being filled with UHPC-CA units of the same size; the tiling pattern frame is made of silicone rubber with an elastic modulus of 3 MPa and a Shore hardness of A70. like Figure 1 As shown, the tessellation pattern simulates the hexagonal shape of biological structures such as turtle shells. Based on this, the multi-unit interlocking and constraint mechanism of the biomimetic design can enhance the overall protection capability, thereby improving the protection capability against projectile 3.
[0045] like Figure 1As shown, the height of the tiling pattern frame 1 and the UHPC-CA unit 2 is 50mm, that is, the overall thickness of the composite protective device is 50mm. The side length of the regular hexagonal UHPC-CA unit 2 is 150mm. The narrowest distance between opposite sides of adjacent UHPC-CA units 2 is 10mm, that is, the narrowest wall thickness of the tiling pattern frame 1 is 10mm. The tiling graphic frame and UHPC-CA cells are spliced together via lateral male and female slots, such as... Figure 3 As shown, the groove 11 in the male and female slots is set on the side of the tiling pattern frame 1. The recess depth from the side is 5mm. The length of the groove 11 is the same as that of the regular hexagon. The width of the groove 11 is 20mm. The groove 11 is located in the middle of the side of the tiling pattern frame 1. The boss is set on the side of the UHPC-CA unit 2. The size of the boss is the same as that of the groove 11. The shape and position of the boss match the UHPC-CA unit. Then the wall thickness of the tiling pattern frame 1 is more than 15mm, and the wall thickness at the recess of the groove is 10mm.
[0046] The raw materials for preparing the UHPC-CA unit include 400 parts cement, 40 parts silica fume, 40 parts fly ash, 900 parts river sand, 900 parts basalt coarse aggregate, 39 parts steel fiber, 120 parts water and 8 parts water-reducing agent.
[0047] The gaps between the tiling pattern frame and the UHPC-CA unit are filled with UHPC material. Compared with the raw materials used to prepare the UHPC-CA unit, the UHPC material used for filling does not contain coarse aggregate or steel fiber.
[0048] The cement is 52.5 ordinary Portland cement.
[0049] The silica fume has a silica mass percentage of not less than 97%, a pozzolanic activity index greater than 95%, a specific surface area greater than 21.0 m² / g, and a density of 2.20 g / cm³.
[0050] The fly ash is Class I fly ash, with a loss on ignition of less than 3.0% and a specific surface area of more than 1000 cm² / g, mainly containing silicon dioxide and aluminum oxide.
[0051] The fine aggregate is natural river sand with a fineness modulus of 2.3 and a maximum particle size of 4.75 mm.
[0052] The coarse aggregate is high-strength and high-hardness basalt coarse aggregate with a particle size of 5~8mm.
[0053] The steel fibers are straight and 13mm in length.
[0054] The water-reducing agent is a polycarboxylate water-reducing agent with a water reduction rate of >30%.
[0055] The preparation method includes the following steps: S1. Use rigid plastic to prepare the molding die for the UHPC-CA unit, such as... Figure 2 As shown, the inner cavity of the molding die is a regular hexagon, and the side is provided with grooves for forming the bosses in the male and female grooves. The inner cavity of the molding die is consistent with the shape of the UHPC-CA unit.
[0056] Then, the raw materials for the UHPC-CA unit are prepared in proportion, poured into the molding mold, and cured, including the following steps: S11. Mix cement, fly ash, silica fume, fine aggregate and coarse aggregate, and dry mix at a speed of 60 r / min for 2 min to obtain dry mix; S12. Add water and water-reducing agent to the dry mix, and stir initially at 120 r / min for 4 min to make the mixture exhibit good uniformity and workability. Then, gradually and evenly sprinkle in steel fibers and stir at 120 r / min for 4 min to obtain UHPC-CA slurry. S13. Stir the UHPC-CA slurry at 150r / min for 3 minutes, then pour it into a rigid mold. Use a scraper and vibrator to remove air bubbles and improve density. Vibrate the vibrator at 30Hz for 3 minutes. The standard curing temperature is 20±2℃ and the humidity is ≥95%. After curing and demolding, perform surface treatment and size adjustment, and use a concrete grinder to polish the surface to eliminate defects.
[0057] S2. A tessellation pattern frame made of silicone rubber is prepared by injection molding.
[0058] S3. The closely spaced graphic frame undergoes elastic deformation to expand the internal cavity size. The UHPC-CA units are then assembled one by one, and the gaps are filled with UHPC slurry to ensure the overall structure’s robustness and stability. Finally, the assembly of the composite protective device is completed.
[0059] Example 2 A composite protective device includes a tessellated pattern frame comprising multiple equilateral triangular cavities of the same size, each cavity being filled with a UHPC-CA unit of the same size; the tessellated pattern frame is made of nitrile rubber with an elastic modulus of 8 MPa and a Shore hardness of A80.
[0060] The raw materials for preparing the UHPC-CA unit include 360 parts cement, 36 parts silica fume, 36 parts fly ash, 800 parts fine aggregate, 800 parts coarse aggregate, 39 parts steel fiber, 120 parts water, and 5 parts high-efficiency water-reducing agent. The specifications of each raw material are the same as in Example 1, and the preparation method is the same as in Example 1.
[0061] Example 3 A composite protective device includes a tiling pattern frame comprising multiple quadrilateral cavities, each cavity being filled with UHPC-CA units of the same size; the tiling pattern frame is made of silicone rubber with an elastic modulus of 1 MPa and a Shore hardness of A30; the overall thickness of the device and the shape of the male and female grooves are the same as in Example 1.
[0062] The raw materials for preparing the UHPC-CA unit include 520 parts cement, 52 parts silica fume, 52 parts fly ash, 1000 parts fine aggregate, 1000 parts coarse aggregate, 78 parts steel fiber, 130 parts water, and 10 parts high-efficiency water-reducing agent. The specifications of each raw material are the same as in Example 1, and the preparation method is the same as in Example 1.
[0063] Example 4 A composite protective device, comprising a tiled pattern frame and a UHPC-CA unit, having the same shape, structure, and dimensions as Embodiment 1, has the same appearance as... Figure 4 Same; in such Figure 4 The cross-section at position AA in the middle is as follows Figure 5 As shown, the cross-section of the tiling pattern frame includes a rigid metal skeleton 4 and an elastic material 12. The rigid metal skeleton 4 is made of high-strength steel, and the outer periphery of the rigid metal skeleton is covered with the same elastic material 12 as in Example 1. The narrowest distance between opposite sides of adjacent UHPC-CA units 2 is 10mm, and the average thickness of the rigid metal skeleton 4 in this direction is 5mm.
[0064] The raw materials used to prepare the UHPC-CA unit are the same as those in Example 1.
[0065] In the preparation method, a rigid metal skeleton 4 is first prepared, and then an elastic material 12 is added to the periphery of the rigid metal skeleton 4 by injection molding to obtain a tiled pattern frame.
[0066] The other steps are the same as in Example 1.
[0067] Example 5 A composite protective device includes a tiling pattern frame and a UHPC-CA unit, having the same shape, structure, and dimensions as in Embodiment 1, such as... Figure 6 In the cross-section shown, the tiling pattern frame includes a rigid metal skeleton, which includes seven hexagonal borders 41. Adjacent hexagonal borders 41 are connected by a mortise and tenon structure. The material of the hexagonal borders 41 is the same as that of the rigid metal skeleton 4 in Embodiment 4. The hexagonal borders 41 and the internal UHPC-CA units 2 are separated by the same elastic material 12 as in Embodiment 1. The narrowest distance between opposite sides of adjacent UHPC-CA units 2 is 10mm. The average thickness of the hexagonal borders in this direction is 4mm. There are two sidewalls of hexagonal borders 41 between adjacent UHPC-CA units 2.
[0068] In the preparation method, a hexagonal frame 41 is first prepared, and then an elastic material 12 is added to the inside of the hexagonal frame 41 by injection molding. Multiple hexagonal frames 41 are then connected to obtain a tiled graphic frame.
[0069] The other steps are the same as in Example 1.
[0070] Comparative Example 1 A composite protective device includes a tiling pattern frame and a UHPC-CA unit, having the same shape, structure and size as in Embodiment 1, and the material of the tiling pattern frame is the same as in Embodiment 1.
[0071] The raw materials for preparing the UHPC-CA unit are 590 parts cement, 150 parts silica fume, 150 parts fly ash, 1100 parts river sand, 39 parts steel fiber, 222 parts water, and 15 parts water-reducing agent. Coarse aggregate is not included. The specifications of other raw materials are the same as in Example 1.
[0072] The preparation method is the same as in Example 1, but no coarse aggregate is added during the preparation of the UHPC-CA unit.
[0073] Comparative Example 2 A protective device having the same shape, structure and size as in Example 1, but excluding the tiling graphic frame, is a sheet material integrally cast from UHPC-CA material in one piece.
[0074] The raw materials used to prepare the UHPC-CA material in this comparative example are the same as those in Example 1.
[0075] Comparative Example 3 A protective device having the same shape, structure and size as in Example 1, except that thermoplastic resin is used as the adhesive in S3.
[0076] Experimental Example The test for resistance to high-speed projectile penetration includes the following steps: 1) Targets were prepared using the composite protective device of Example 1, the composite protective device of Comparative Example 1, and the protective device of Comparative Example 2, respectively. The thickness in the ballistic direction was 50 mm, which is a single-layer device. A pointed oval projectile with a diameter of 8 mm was selected. The projectile material was 30CrMnSiNi2A high-strength alloy steel (yield strength of 1370-1466 MPa, ultimate strength of 1770 MPa, Rockwell hardness of 55 HRC).
[0077] 2) Use the gun barrel to launch a pointed oval projectile, which strikes the target at an impact velocity of 400 m / s. Use a high-speed camera on the side of the trajectory to capture the projectile's motion and collect relevant data.
[0078] 3) The damage to the high-speed projectile target was assessed by measuring the penetration depth, crater diameter, and crater volume. The results are shown in Table 1; where the target is... Figure 4 The protective device shown includes a tiling pattern frame and UHPC-CA units; penetration depth refers to the distance from the impact surface of the target to the deepest point of the crater; crater diameter is the diameter of an equivalent circle with the same area as the target crater; crater volume refers to the volume of the target crater.
[0079] Table 1 Test results of resistance to high-speed projectile penetration
[0080] As shown in Table 1, the penetration depth of Example 1 was 23.5 mm, significantly better than that of Comparative Example 1 (42.7 mm), Comparative Example 2 (35.3 mm), and Comparative Example 3 (40.5 mm). Example 1 employed a biomimetic structural splicing method combined with a highly elastic polymer energy-absorbing framework, which greatly improved the material's penetration resistance. Through this biomimetic design, the hexagonal UHPC-CA units could mutually restrict lateral displacement, reducing the transfer of projectile impact energy, and the penetration depth was further reduced through the closely spaced patterned framework (energy-absorbing material). While Comparative Example 2 resembled the Example 1 in appearance, it lacked energy-absorbing material and used integrated casting, resulting in a single stress transmission path and lacking the advantages of a biomimetic structure, leading to a significant decrease in penetration resistance.
[0081] The area and volume of the impact crater in Example 1 were 60820 mm² and 91250 mm³, respectively, significantly smaller than those in Comparative Example 1 (78460 mm² and 120550 mm³), Comparative Example 2 (67900 mm² and 108300 mm³), and Comparative Example 3 (75300 mm² and 115000 mm³). This indicates that the spliced biomimetic structure and energy-absorbing frame in Example 1 not only effectively prevented deep penetration of the projectile but also significantly reduced the range and volume of the impact crater. The highly elastic polymer frame can absorb some energy during impact, reducing the concentration of impact force in local areas and minimizing the damage range. Although Comparative Example 2 was identical in shape to the Example 1, the lack of energy-absorbing material and the integrated casting resulted in the impact force spreading over a larger area, failing to achieve the local energy absorption effect of the spliced biomimetic design, leading to a larger damage range. Comparative Example 3 used thermoplastic resin as a binder. Due to its weak bonding performance, the force transmission efficiency between the unit and the frame was low, and the stress was not effectively dispersed to the energy-absorbing material of the frame, resulting in stress concentration in local areas and further expanding the damage range.
[0082] The area and volume of the crater on the back surface reflect the degree of local damage to the target. In Example 1, the crater area on the back surface is 20100 mm², and the volume is 13600 mm³, significantly smaller than those in Comparative Example 1 (33650 mm² and 22950 mm³) and Comparative Example 2 (28750 mm² and 18800 mm³). The energy-absorbing frame in the spliced biomimetic design plays a crucial role in resisting impact, effectively preventing cracks from propagating outward and confining them to the impacted local area. In Comparative Example 2, although the appearance is the same as the example, the lack of local splicing and energy-absorbing frame due to the integrated casting method allows cracks to easily spread to the surrounding area, causing greater damage. In Comparative Example 3, although the thermoplastic resin can tightly bond the UHPC-CA unit and the frame, its bonding performance is inferior to UHPC, resulting in poor force transfer between each unit and the frame. This leads to uneven stress distribution, significant stress concentration, and consequently, a larger damage area.
[0083] The design concept of biomimetic structures originates from the polygonal protective systems found in nature, such as the scales of tortoise shells and pangolins. Through the splicing of regular hexagonal units and the application of energy-absorbing materials, a significant improvement in penetration resistance is achieved. The biomimetic structure in Example 1 not only reduces the transmission of lateral stress during impact through constraints at the splicing points, but also further weakens the impact through the energy absorption effect of the highly elastic polymer framework. This design enables the material to exhibit superior performance in resisting high-speed projectile impacts, making it particularly suitable for military protection and the protection of critical infrastructure.
[0084] In contrast, while Comparative Example 2 mimics the appearance of a biomimetic structure, its integrated casting design fails to effectively limit the propagation of radial cracks. Lacking the advantages of energy-absorbing materials, stress diffuses extensively within the impact zone, reducing overall penetration resistance. Therefore, it can be concluded that the true advantage of a biomimetic structure lies in its modular design and localized energy-absorbing framework, which not only improves penetration resistance but also reduces the area and volume of damage.
[0085] Examples 4 and 5, based on Example 1, add a rigid metal frame. This design significantly enhances the structural stability and penetration resistance of the composite protective device. The rigid metal frame effectively disperses impact force by increasing the overall rigidity of the device, reducing localized penetration and structural deformation. It also strengthens the connections between individual units, preventing damage or detachment of the device under impact. Furthermore, the metal frame optimizes energy absorption and dispersion, limiting crack propagation. Compared to Example 1, the addition of the rigid metal frame significantly improves the composite protective device's impact resistance, durability, and maintainability, especially in the face of high-energy impacts, where its overall performance is effectively enhanced.
[0086] Overall, Example 1, through the combination of a modular biomimetic design and energy-absorbing materials, significantly improves the impact and penetration resistance of UHPC-CA. Compared with Comparative Examples 1, 2, and 3, Example 1 not only demonstrates superior performance in terms of penetration depth, impact area, and volume, but also exhibits more effective control over the back surface. The unique advantages of biomimetic design lie in localized constraint and energy absorption, fully leveraging the material's impact resistance potential. It is suitable for the construction of military protective facilities, critical infrastructure, and high-risk areas, providing a higher level of protection and possessing broad engineering prospects in practical applications.
[0087] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A composite protective device, characterized in that, It includes a tiled graphic frame and UHPC-CA units filled in the tiled graphic frame; the tiled graphic frame and the UHPC-CA units are laterally spliced; the tiled graphic frame includes a rigid metal skeleton, and the rigid metal skeleton and the UHPC-CA units are separated by an elastic material, the elastic material being silicone rubber or nitrile rubber; The rigid metal frame is covered with an elastic material; or... The rigid metal frame includes multiple interlocking polygonal borders, with elastic material spaced between the polygonal borders and the internal UHPC-CA units. The rigid metal skeleton is made of high-strength steel, with a tensile strength of 600~1200 MPa and a yield strength of 500~1000 MPa. The elastic modulus of the elastic material is between 0.1 and 10 MPa, and the Shore hardness is A30 to A80. The tiling pattern frame and the UHPC-CA unit are spliced together by lateral male and female grooves. The male and female grooves include grooves and bosses, and the height of the bosses is the same as the depth of the grooves. The gap between the UHPC-CA unit and the tiling pattern frame is filled with UHPC material; no coarse aggregate and steel fiber are added to the UHPC material, and the other raw materials are the same as those used to prepare the UHPC-CA unit; The raw materials for preparing the UHPC-CA unit include 360-520 parts of cement, 36-52 parts of silica fume, 36-52 parts of fly ash, 800-1000 parts of fine aggregate, 800-1000 parts of coarse aggregate, 39-78 parts of steel fiber, 120-130 parts of water, and 5-10 parts of high-efficiency water-reducing agent.
2. The composite protective device according to claim 1, characterized in that, The shape of the tessellation frame is one or more of triangles, hexagons, and squares.
3. A method for preparing the composite protective device according to any one of claims 1-2, characterized in that, Includes the following steps: S1. Prepare UHPC-CA units of a predetermined shape; S2. Prepare a tiling pattern framework of elastic material; S3. Assemble the UHPC-CA unit into the tiled pattern frame to obtain the composite protection device.
4. The method for preparing the composite protective device according to claim 3, characterized in that, In S1, UHPC-CA units are cast in a rigid mold, the inner cavity of which has the same shape as the inner cavity of the tiled graphic frame.
5. The method for preparing the composite protective device according to claim 3, characterized in that, In S1, the preparation method of the UHPC-CA unit includes: S11. Mix cement, fly ash, silica fume, fine aggregate and coarse aggregate in a dry mix to obtain a dry mix material; S12. Add water and high-efficiency water-reducing agent to the dry mixture, stir initially, then add steel fibers and stir evenly. S13. Pour the UHPC-CA slurry into a rigid mold, remove air bubbles, and then cure it.
6. The method for preparing the composite protective device according to claim 3, characterized in that, In S3, UHPC material is filled into the gaps between the UHPC-CA unit and the tiled pattern frame, and the composite protective device is obtained after the material is cured.
7. The application of the composite protective device according to any one of claims 1-2, characterized in that, The application includes applications within protective facilities.
Citation Information
Patent Citations
Anti-penetration ultra-high performance concrete as well as preparation method and application thereof
CN117756473A
Armor structure and preparation method thereof
CN118602860A
Fabricated reinforcing structure and method for improving anti-penetration explosion protection performance of dam
CN119083383A